An Empirical Investigation on Practicing Secure Software Development in Software Development Life Cycle in Small & Medium Level Software Firms in Bengaluru - Sandhya Soman, Dr. Piyush Kumar Pareek, Veeranna Kotagi (International Journal of Advanced Science and Technology, 2020)
Software security is a basic necessity for software frameworks. Notwithstanding, late examination shows that numerous software development systems don't expressly incorporate strategies for consolidating data security into the software development life cycles (SDLC). This exploration researches, utilizing poll survey, the philosophies being utilized in software developme nt in Bengaluru small and medium software firms and portrays a model for incorporating security into the SDLC. The point is to recognize the suitable methods for presenting security gauges a lot prior in the SDLC. The examination recognized different significant components as security measures, arrangements, forms being drilled, and devices utilized inside SDLC ventures. In such manner, proposals and confirmation were accumulated to inspire the real exercises that are suitable to be led at each period of SDLC.